2015
DOI: 10.1007/s00226-015-0792-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macromolecular interactions in the cell walls of hardwood, softwood and maize by fluorescence and FTIR spectroscopy, differential polarization laser scanning microscopy and X-ray diffraction

Abstract: We compared interactions between macromolecules in the cell walls of different plant origin, namely spruce wood (Picea omorika (Pančić) Purkiňe) as an example of softwood, maple wood (Acer platanoides L.) -a hardwood and maize stems (Zea mays L.) -a herbaceous plant from the grass family and widely used agricultural plant. We compared macromolecules' interactions in isolated cell walls from the three species by using Fourier transform infrared spectroscopy, X-ray diffraction and fluorescence spectroscopy. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Taking advantage of the high precision, quantitative FDLD values obtained from DP-LSM imaging ( Figure 7 ), anisotropic features of different plant cell walls (hardwood: maple— Acer platanoides L., softwood: spruce— Picea omorika (Pančic) Purkyne and maize— Zea mays L.) can be compared [ 51 ]. This was performed via analysing the distribution of FDLD values indicating the degree of order in the cell walls.…”
Section: Applications In Plant Cell Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the high precision, quantitative FDLD values obtained from DP-LSM imaging ( Figure 7 ), anisotropic features of different plant cell walls (hardwood: maple— Acer platanoides L., softwood: spruce— Picea omorika (Pančic) Purkyne and maize— Zea mays L.) can be compared [ 51 ]. This was performed via analysing the distribution of FDLD values indicating the degree of order in the cell walls.…”
Section: Applications In Plant Cell Researchmentioning
confidence: 99%
“…The blue and yellow regions in FDLD images are for the horizontal and the vertical dipole orientations, respectively. (Reproduced in colour from [ 51 ], with permission from Springer Nature).…”
Section: Figurementioning
confidence: 99%
“…The successive substitution of hydroxyl groups by acetyl groups during acetylation was confirmed by the FTIR spectra based on the emergence and/or the increasing intensity of the band at 1740 cm −1 (C=O stretching) and the decrease in the intensity of vibrations in the OH-region (around 3750-3000 cm −1 ) (Bian et al 2010;Belmokadden et al 2011) (Figure 1). The OH-region is due to several stretching vibrations of inter-and intra-molecular hydrogen bonds (Popescu et al 2011;Djikanović et al 2016), for example, involving the O(2)H and the O(3)H in the xylan chain. The combination of such vibrations causes a broadening of the OH region in the FTIR spectra (Papescu et al 2011).…”
Section: Acetylation Of Xylan Samples: Influence Of Reaction Conditionsmentioning
confidence: 99%
“…FT-IR deconvolution of hydroxyl groups band was adopted in order to study the changes of the energy of H-bonds and the H-bonding distance during delignification [13] or the deconstruction of cellulose [14]. Moreover, it was used to study the differences of the content of H-bonds not only between dislocation region and normal region [15], but also among plant species [16,17]. Regarding the changes of H-bonding network during PFI refining, Yuan et al [18] reported that the content of H-bonds and crystallinity index (CI) of eucalyptus fibers changed with the increment of beating time.…”
Section: Introductionmentioning
confidence: 99%